Fetal Outcome in Patients with Pre-Eclampsia at Ayub Teaching Hospital Abbottabad - Seema Rafiq, Atyya Bibi Khan, Uzma Bibi, Nadia Bibi, Zahida Parveen (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of fetal outcome in patients presented with pre-eclampsia. Study design: Descriptive cross-sectional study Place and duration of study: Department of Obstetrics & Gynecology, Ayub Teaching Hospital Abbottabad from 4th May 2020 to 4th November 2020. Methodology: One hundred and twenty six pre-eclamptic patients aged 18-45 years having gestational age more than 20 weeks were enrolled. Detailed demographics were recorded after taking informed written consent. Fetal outcomes were examined. Data was analysed by SPSS 22.0. Results: Mean age of patients was 27.48±5.618 years with mean gestational age of 35.056±2.9554 ranging from 31.2 to 41.1 weeks. Mean systolic blood pressure was 151.98±8.85 and mean diastolic blood pressure was 96.90±4.64. Mean proteinuria was 170.56±105.92. The frequency of preterm birth was 26 (20.6%), LBW was found in 52.4% patients, IUGR was found in 25.4%, birth asphyxia was found in 19% patients and still birth was found in 16.7%. Conclusion: Pre-eclampsia can lead to major fetal and maternal complications. We found in our study that low birth weight, preterm birth and IUGR were the most common adverse fetal outcomes. Keywords: Fetal outcome, Birth asphyxia, Stillbirth, Preterm birth, Low birth weight, Pre-eclampsia